Rapid and Simple Method for the Most-Probable-Number Estimation of Arsenic-Reducing Bacteria - Kuai, Linping (American Society for Microbiology, 2001)
A rapid and simple most-probable-number (MPN) procedure for the enumeration of dissimilatory arsenic-reducing bacteria (DARB) is presented. The method is based on the specific detection of arsenite, the end product of anaerobic arsenate respiration, by a precipitation reaction with sulfide. After 4 weeks of incubation, the medium for the MPN method is acidified to pH 6 and sulfide is added to a final concentration of about 1 mM. The brightly yellow arsenic trisulfide precipitates immediately and can easily be scored at arsenite concentrations as low as 0.05 mM. Abiotic reduction of arsenate upon sulfide addition, which could yield false positives, apparently produces a soluble As-S intermediate, which does not precipitate until about 1 h after sulfide addition. Using the new MPN method, population estimates of pure cultures of DARB were similar to direct cell counts. MPNs of environmental water and sediment samples yielded DARB numbers between 10(1) and 10(5) cells per ml or gram (dry weight), respectively. Poisoned and sterilized controls showed that potential abiotic reductants in environmental samples did not interfere with the MPN estimates. A major advantage is that the assay can be easily scaled to a microtiter plate format, enabling analysis of large numbers of samples by use of multichannel pipettors. Overall, the MPN method provides a rapid and simple means for estimating population sizes of DARB, a diverse group of organisms for which no comprehensive molecular markers have been developed yet.